CONTENT ANALYSIS OF WHEN ENGLISH RINGS A BELL STUDENT’S TEXTBOOK - Maria Melati Sitorus; Lauren Hotmauli Silalahi; Hana Rajagukguk; Erikson Saragih (University of Kuningan, 2021)
This study's objective was for analyzing materials relevance in psychomotor and cognitive-based on 2013 English curriculum of competence in Textbook of the eighth grade of junior high school